2015
DOI: 10.1614/ipsm-d-14-00062.1
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide Treatment and Application Method Influence Root Sprouting in Chinese Tallowtree (Triadica sebifera)

Abstract: Chinese tallowtree is an invasive tree found throughout the southeastern United States and in California. Its negative effects can be seen in numerous natural and managed ecosystems, including bottomland hardwood forests, pastures, pine plantations, and along lakes, ponds, streams, and rivers. Despite its troublesome presence for many decades, relatively few effective control strategies are available. Root sprouting following management efforts is a major impediment to successful control. Studies were conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Aminocyclopyrachlor, a relatively new herbicide labeled for use in non-crop settings, controls a wide range of weeds and invasive plants (Enloe et al 2015; Minogue et al 2011). It primarily has activity on eudicots, but some grasses have demonstrated sensitivity to it (Flessner et al 2011c; Wirt and Lym 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Aminocyclopyrachlor, a relatively new herbicide labeled for use in non-crop settings, controls a wide range of weeds and invasive plants (Enloe et al 2015; Minogue et al 2011). It primarily has activity on eudicots, but some grasses have demonstrated sensitivity to it (Flessner et al 2011c; Wirt and Lym 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Vegetative regeneration has been identified as a major driver of invasiveness and a major hurdle to control and eradicate not only for woody plants Hamilton 1997, Rolim et al 2015), but also for herbaceous plants (Burns 2006, Marco et al 2010, Rolim et al 2015, Klinerov a et al 2018. In fact, prolific resprouting is one of the most challenging traits for invasive control, as it is a major driver of reinvasion and persistence, prompting a body of research dedicated to the management of resprouting through specialized chemical treatments (Witkowski and Garner 2008, Coffman et al 2010, Const an-Nava et al 2010, Enloe et al 2015, Espeland et al 2017). On the other hand, the importance of uniparental reproduction for the establishment of exotic species outside their range was first recognized by Baker (1955).…”
Section: Discussionmentioning
confidence: 99%
“…When targeting large individuals of Chinese tallow, injection appeared to be a more effective method of herbicide application than foliar applications (Johns et al, 1999), and the highest plant mortality occurred when herbicide was assimilated into perennating buds and organs (Bóo and Pettit, 1975;Wilson et al, 1975;Sosebee, 1983). In a study investigating several herbicide treatment methodologies for Chinese tallow (cut stump, basal bark, and foliar) using aminocyclopyrachlor (DuPont, Wilmington, DE), aminopyralid (Milestone VM™, Dow AgroSciences), fluroxypyr (Vista XRT™, Dow AgroSciences, Indianapolis, IN), imazamox (Clearcast™, BASF, Research Triangle Park, NC), triclopyr amine (Garlon 3A™, Dow AgroSciences), and triclopyr ester (Garlon 4™, Dow ArgoSciences), only triclopyr (ester and amine formulations) did not provide consistent control of root collar and lateral root sprouting (Enloe et al, 2015). In a study on the efficacy of imazapyr, triclopyr, and glyphosate using 'hack and squirt' application methodology, Gresham (2010) found that all three herbicides were effective on Chinese tallow with no residual effects on untreated native live oak (Quercus virginiana Mill.)…”
Section: Herbicidementioning
confidence: 99%